Língua Portuguesa na segunda metade do século XIX: sintaxe do advérbio em uma perspectiva historiográfica - Almeida, Wemylla de Jesus (2015)
This research reflects on the syntax of the teaching process of the Portuguese language, in particular, the adverb function in Brazil in the second half of the nineteenth century. We seek to trace the historiographical paths in learning, taking as corpus Syntax study work and construction of the Portuguese Language, Thomaz da Silva Brandão (1888). In this perspective, the theoretical foundation of our work is the Historiography Language (HL), specifically, Koerner (1996), based on its three principles: context, mapping the climate of opinion, the spirit of the time, immanence establishing an overview of the theory and terminology used in the works and, fitness, introducing modern approaches of technical vocabulary, from the analysis. Therefore, for the adjustment, use the work of New study lessons of syntactic analysis, Adriano da Gama Kury (1999) in order to contribute to the development of the Portuguese language teaching in elementary school. Thus, our main objectives are to explain how his gave the study of syntax, especially, the adverb function to the implementation process of the Portuguese language in the second half of the nineteenth century, in Thomaz grammar studies da Silva Brandão (1888) and Adriano da Gama Kury (1999), the twentieth century also explain the deployment process of a language policy in a historiographical approach. As a result of our research, we also noticed that the works analyzed contributed greatly to the implementation of the syntax of the words of the Portuguese language, since there are gaps in the teaching of adverb function that need to be filled